(untitled) (Eurasian Scientific Herald, 2022)
Parkinson’s disease is the most common neurodegenerative disease in the world, which requires a comprehensive study of this disease, as well as the prevention of its complications. The article discusses the impairment of the cognitive status of patients with Parkinson’s disease using the MMSE and FAB test tests, as well as the effect of the drug memantine hydrochloride on the cognitive status.